Investigative Approach On Teaching Methods Of Japanese Modern Language - Mulekova Linara Ramilevna (Euro Asian Journal Publishing, 2024)
This article analyses an investigative and analytical approach on teaching methods of Japanese modern language. Besides, the paper researches the reflection of research and application of modern Japanese teaching methods. Methods of teaching Japanese have developed rapidly, especially in the previous 30 years. As a language learner, training manager, or teacher, it is important to understand the various methods and techniques so that you are able to navigate the market, make educated choices, and boost your enjoyment of learning a language.
Keywords: Japanese modern language; methods and techniques; multimedia; communicative approach